PENYELESAIAN KREDIT MACET PADA PT. BANK RAKYAT INDONESIA, Tbk CABANG UNIT MULYOSARI SURABAYA - Idayati, Farida (Jurnal Ilmiah Manajemen dan Bisnis (JIMBis), 2022)
This study aims to resolve bad or non-performing loans carried out by banks to debtors who have no prospects in trying and have good intentions in solving them. The settlement of bad debts is carried out peacefully or through legal channels. If the credit is already bad, the bank must settle the credit in various settlements. The method used in this research is to use qualitative methods and in the preparation of this study the authors conducted case and field studies at PT. BRI, Tbk at the Mulyosari Unit Branch Surabaya. In this study the characteristics of the problem related to the background and current condition of the object under study and certain aspects or functions of the company. Case Study Research analyzes in depth about certain conditions and situations to determine alternative solutions for companies experiencing bad loans.The result of this research is that if there are things that cause a jammed collateral to occur at PT. BRI, Tbk. Unit Mulyosari Surabaya branch then by completing the credit. Settlement here does not mean that all non-performing loans must be confiscated by collateral, but are resolved starting peacefully until they enter the realm of law, if the debtor does not have good intentions to solve his credit problems. The next settlement effort can be administratively first, namely resolving the collateral that is experiencing problems before a lawsuit is made to the court/judgment to carry out the execution of the objects that are guaranted.